2006
DOI: 10.1111/j.1471-4159.2006.03799.x
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline neuroprotects, reduces microgliosis, and inhibits caspase protease expression early after spinal cord injury

Abstract: Minocycline, a clinically used tetracycline for over 40 years, crosses the blood-brain barrier and prevents caspase up-regulation. It reduces apoptosis in mouse models of Huntington's disease and familial amyotrophic lateral sclerosis (ALS) and is in clinical trial for sporadic ALS. Because apoptosis also occurs after brain and spinal cord (SCI) injury, its prevention may be useful in improving recovery. We analyzed minocycline's neuroprotective effects over 28 days following contusion SCI and found significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(130 citation statements)
references
References 80 publications
6
122
0
2
Order By: Relevance
“…In the present study, we used an animal model of thoracic spinal cord injury to better characterize the effect of minocycline on neuroglial activation, both at the primary injury site and additional caudal levels. Consecutive rostral-caudal spreading of secondary lesion was commonly asymmetrical, with the extent of cavitation at post-injury day 28 greater caudally than rostrally 10) . With regard to potential SCI therapies in humans, animals treated with minocycline exhibited an improved recovery of motor function after hemisection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used an animal model of thoracic spinal cord injury to better characterize the effect of minocycline on neuroglial activation, both at the primary injury site and additional caudal levels. Consecutive rostral-caudal spreading of secondary lesion was commonly asymmetrical, with the extent of cavitation at post-injury day 28 greater caudally than rostrally 10) . With regard to potential SCI therapies in humans, animals treated with minocycline exhibited an improved recovery of motor function after hemisection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these authors also demonstrated that minocycline both inhibited the expression of p75 neurotrophin receptors and the activation of Ras homolog gene family member A (RhoA) after SCI. More recently, Festoff et al reported that minocycline also might exert a neuroprotective effect in SCI by reducing microgliosis and inhibiting caspase expression 10) . In combination, this emerging data suggests that minocycline may protect the spinal cord from secondary damage after SCI via several unique pharmacologic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspases are proteases involved in apoptosis, necrosis, and inflammation (Eldadah et al, 2000). After administration of minocycline, a significant decrease in caspase-3 and apoptosis was seen in moderate contusion SCI in rats (Festoff et al, 2006). Additionally, in another contusion model of SCI in rats, inhibitiory action of oxidative stress was observed following minocycline administration, specifically lipid peroxidation (Sonmez et al, 2013).…”
Section: Search Strategymentioning
confidence: 99%
“…Indeed, neuroprotection by minocycline has been observed in various animal models of PD, HD, ALS, MS, cerebral ischemia, spinal cord injury and traumatic brain injury. 85,95,96 The precise mechanism of minocycline's neuroprotective effects remains unclear. It is known, however, that minocycline is a potent inhibitor of caspase-related apoptotic pathways.…”
Section: Currentmentioning
confidence: 99%